Radiation evangelists : technology, therapy, & uncertainty at the turn of the century - Womack, Jeffrey (Jeffrey C.) (University of Pittsburgh Press, 2020)
Radiation Evangelists explores X-ray and radium therapy in the United States and Great Britain during a crucial period of its development, from 1896 to 1925.